RADICAL FEMINISM IN EKA KURNIAWAN’S NOVEL BEAUTY IS A WOUND - Thesya Widya; Asnani Asnani (JOURNAL OF LANGUAGE, 2020)
This research brings about radical feminism and the role and position of women as pimps. The analysis of this research is fulfilled by using descriptive qualitative research in which the data and the finding of the research are presented and described in a form of description.  In this research, radical feminism was revealed in the life of a woman by the name of Dewi Ayu who worked as a prostitute during Japanese colonialism in a warehouse named Mama Kalong Place. Mama Kalong who worked as a pimp served Japanese soldiers in the whorehouse played to make a price for prostitutes. Mama Kalong gave a good shelter and well care to the women in order that they remained healthy and fresh so that they would be ready anytime they were needed. Unfortunately, the pimp did not give the women any protection from any harms which are very possible to befall upon the women. The finding of this research shows that the life of women in colonialism under a pimp is really oppressed. Oppression, suffering, and injustice are with them in the whole life.